Relação da angiogênese e da densidade de mastócitos com a fibrose miocárdica em idosos com cardiopatia chagásica crônica - Vilela, Joana Estela Rezende (2015)
In Americas million people are carriers of Chagas disease caused by Trypanosoma cruzi. Chronic chagasic cardiopathy is the most severe form of the disease, characterized by lesions in the myocardium associated with inflammation and fibrosis which often evolve to progressive decrease of heart function. Chagas’ disease during aging may have specific aspects that require further studies. The aim of the study was to describe the relationship of angiogenesis and mast cell density with myocardial fibrosis in elderly patients with chronic Chagas' disease. To reach this goal we selected left ventricular fragments of autopsied patients at the Clinical Hospital, Federal University of Triangulo Mineiro. The samples were divided into four groups: elderly with chagasic cardiopathy - 6 (CC elderly); elderly without chagasic cardiopathy - 5 (SC elderly); Non-elderly with chagasic cardiopathy - 5 (no elderly CC); Non-elderly without chagasic cardiopathy - 5 (no elderly SC). Picrosirius red staining was performed for quantifying the percentage of collagen in common light and 10x magnification. Immunohistochemistry was performed to obtain the mast cell density, using antitriptase monoclonal antibody, and the density of blood vessels, using CD34 monoclonal antibody. The samples were evaluated under common light and at 40x magnification. The percentage of collagen was significantly higher in the elderly CC group compared to the other groups (p = 0.003). The density of mast cells was higher in elderly CC group, but no significant difference (p = 0.226). The density of blood vessels was lower in the elderly CC group and no significant difference (p = 0.224). Therefore, in elderly CC group there was more collagen, and also higher density of mast cells and lower density of blood vessels, although not significant, which are probably associated to the etiopathogenesis of myocardial lesions in chronic Chagas' disease during aging.